0290 Objective Sleep Indices Relative to Neurocognitive Function and Cerebrospinal Fluid Biomarkers in Patients with Mild Cognitive Impairment and Alzheimer's Disease. (27th April 2018) - Nawabit, R; Bena, J; Pillai, J; Leverenz, J B; Mehra, R
Abstract: Introduction: Compelling data showed an association of reduced sleep and dementia risk. We hypothesize that even among those with mild cognitive impairment (MCI) stage of Alzheimer's disease (AD), abnormal sleep indices are associated with neurocognitive deficits and cerebrospinal fluid (CSF) AD biomarkers. Methods: Patients with MCI stage of AD (Mini-Mental State Examination>20 and Clinical Dementia Rating Global score <1) underwent collection of neurocognitive measures (Mattis Dementia Rating Scale (DRS-2), Hopkins Verbal Learning Test (HVLT), Digit Span) and CSF AD biomarkers (amyloid β peptide (Aβ42) total tau protein (ttau), phosphorylated tau protein (ptau)). Participants wore 7-day actigraphy (sleep efficiency (SE), total sleep time(TST), sleep fragmentation(SF), nocturnal awakenings(NA)) and home sleep testing (apnea hypopnea index (AHI), oxygen saturation<90%). Associations between sleep indices, neurocognitive scores and AD biomarkers were evaluated using two-sample t-tests or Pearson correlations. For significant relationships, linear models were fit, unadjusted, and then separately adjusted for age, sex, body mass index (BMI) and education (beta coefficients (95% CI) presented). Results: Twenty participants were included who were: age 68.0 ± 6.1 years, 50% fe/male, Caucasian, BMI 27.7 ± 4.6 kg/m 2, AHI= 14.9 ± 9.0, SE 84.8 ± 12.4 and TST: 381.0 ± 116.4. Significant relationships were observed for SE, TST and SF relative to DRS total 0.50(0.04, 0.95), p=0.035, 0.06(0.02, 0.11), p=0.011, and -1.67(-3.08, -0.26), p=0.023, respectively. Significance in adjusted linear models with SE, TST and SF relative to DRS persisted after adjustment for age, BMI, and education (all p<0.05). A significant negative association existed between NA and log-transformed Aβ42: -0.05(-0.10- -0.00), p=0.034, and remained after adjustment for BMI, education, and sex (all p<0.05). Conclusion: This exploratory study demonstrates significant associations across multiple measures of poor sleep quality and cognitive deficits among those with MCI in AD. CSF Aβ42 levels, possibly reflecting degree of AD pathology, correlated with nocturnal awakenings. Further larger studies are needed to verify these results. Support (If Any):